Analisis Penggunaan Bahasa Gaul pada Public Figure Jerome Polin - Fauziah Nur Hasibuan; Karyn Anastasia Siagian; Mia Angelia Fatmawati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The rapid development of communication and information technology in the digital era has brought significant changes in communication patterns and language use, including the use of slang among public figures such as Jerome Polin. This study aims to analyze the use of slang by Jerome Polin with a focus on the types of slang used, the context of its use, and its implications in public communication. The research method used is a qualitative analysis of social media content published by Jerome Polin. The research findings show that the use of slang by public figures can attract followers but also raises concerns about its influence on the development of Indonesian language and culture. The results of this study provide new insights into the phenomenon of slang use among public figures and its influence on the development of Indonesian language, which reflects the dynamics and creativity in language use in the digital era.